2021
DOI: 10.1001/jama.2020.25855
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Behavioral Therapy With In-Clinic or Telephone Group Visits vs In-Clinic Individual Visits on Weight Loss Among Patients With Obesity in Rural Clinical Practice

Abstract: IMPORTANCE Rural populations have a higher prevalence of obesity and poor access to weight loss programs. Effective models for treating obesity in rural clinical practice are needed.OBJECTIVE To compare the Medicare Intensive Behavioral Therapy for Obesity fee-for-service model with 2 alternatives: in-clinic group visits based on a patient-centered medical home model and telephone-based group visits based on a disease management model. DESIGN, SETTING, AND PARTICIPANTS Cluster randomized trial conducted in 36 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(85 citation statements)
references
References 32 publications
3
82
0
Order By: Relevance
“…Results from the PROPEL trial were previously reported; the PROPEL-clinic/phone group produced clinically significant weight loss at 24 months compared with PROPEL-UC (17). Furthermore, results of the REPOWER study indicated that the REPOWERclinic-group intervention produced significantly greater weight loss than the REPOWER-clinic-individual group, but results for the REPOWER-phone-group arm were not significantly different than the REPOWER-clinic-individual group (18). The results of the current investigation are consistent with the conclusions of a recent review that high-intensity behavioral counseling in primary care settings, when delivered in-person, by phone, or electronically, produce clinically significant weight loss (4-7 kg), whereas low-and moderateintensity counseling produce only modest weight loss (1-2 kg) (13).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Results from the PROPEL trial were previously reported; the PROPEL-clinic/phone group produced clinically significant weight loss at 24 months compared with PROPEL-UC (17). Furthermore, results of the REPOWER study indicated that the REPOWERclinic-group intervention produced significantly greater weight loss than the REPOWER-clinic-individual group, but results for the REPOWER-phone-group arm were not significantly different than the REPOWER-clinic-individual group (18). The results of the current investigation are consistent with the conclusions of a recent review that high-intensity behavioral counseling in primary care settings, when delivered in-person, by phone, or electronically, produce clinically significant weight loss (4-7 kg), whereas low-and moderateintensity counseling produce only modest weight loss (1-2 kg) (13).…”
Section: Discussionmentioning
confidence: 73%
“…*Patients who became pregnant, had bariatric surgery, or developed a major illness and/or died were removed from the REPOWER trial a priori; patients who became pregnant, had bariatric surgery, or developed a major illness and/or died were retained in the PROPEL trial, and their data were removed beyond the time the event occurred. PROPEL, Promoting Successful Weight Loss in Primary Care in Louisiana trial; REPOWER, the Rural Engagement in Primary Care for Optimizing Weight Reduction trial outcome in the PROPEL trial was percentage of weight loss from baseline to 24 months, whereas the primary outcome in the REPOWER trial was absolute weight loss (kilograms) from baseline to 24 months (17,18). In the present study, we present results for both outcomes.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Delivering diet and physical activity interventions in group settings (not shared medical appointments) has shown to be effective in promoting weight loss at 12 months or greater 32,33 . A recent large study in rural primary care clinics found that in‐clinic group visits but not telephone‐based group visits, compared with in‐clinic individual visits, resulted in statistically significantly but modest weight loss at 24 months 34 . In our study, those who enrolled in the 20‐week texting program and those who did not enroll in any texting program had significant weight loss.…”
Section: Discussionmentioning
confidence: 99%